Produção semissólida de metarhizium anisopliae e beauveria bassiana em diferentes substratos e efeito da radiação ultravioleta e da temperatura sobre propágulos desses entomopatógenos - Lima, Emma Luize Ottati de [UNESP]; Almeida, J. E. M. de; Gassen, Mariana Hollanda; Wenzel, Inajá Marchizeli; Almeida, Aline Maria Belasco de; Zappelini, Luciano Olmos; Batista Filho, Antonio [UNESP] (My University, 2010)
The present study was aimed to evaluate different (semi-solid) media for the production of Metarhizium anisopliae and Beauveria bassiana propagules, and to evaluate the tolerance of these propagules to ultraviolet radiation and temperature. The experiments were performed at the Biological Control Laboratory of the Instituto Biológico at Campinas, São Paulo, Brazil. For both fungi, 6 repetitions were performed for each of the 17 treatments: corn starch, full rice, parboiled rice, type-1 rice, type-2 rice, oat flakes, canjiquinha [grits], wheat flour, raw cassava flour, yellow corn flour, special wheat flour, corn flour, corn in grains, cassava starch, soy in grains, crushed wheat, and turf. The viability analysis was done in plastic plates containing BDA. For the bioassays involving exposure to ultraviolet light and temperature, BDA was also used for viability analysis, and each treatment was exposed to the UV radiation for 0, 25 and 50 seconds, the temperature exposure being at 20, 25, 30 and 35º C. Using a Potter tower, 2 mL of fungus suspension from each treatment was inoculated to the Diatraea saccharalis caterpillars. Regarding the sporulation, the largest concentrations of M. anisopliae and B. bassiana were found for the treatments with parboiled rice, type-1 rice, type-2 rice, yellow corn flour, corn flour and crushed wheat. The viability of all treatments was superior to 94.00%. Also, the longer the duration of the exposition to the UV, the smaller the number of fertile conidia. At 35o C, a significant loss of conidia viability was observed, and all the treatments presented some level of virulence.

O trabalho teve os seguintes objetivos: 1) avaliar diferentes substratos para a produção semissólida dos fungos Metarhizium anisopliae e Beauveria bassiana; 2) verificar a tolerância dos conídios produzidos ao efeito da radiação ultravioleta e da temperatura; e 3) avaliar a patogenicidade dos conídios a Diatraea saccharalis. Para ambos os fungos, foram utilizadas 6 repetições para cada tratamento: amido de milho, arroz integral, arroz parboilizado tipo1, arroz tipo 1 e 2, aveia em flocos, canjiquinha, farelo de trigo, farinhas de mandioca crua, de milho amarela e de trigo especial, fubá, milho em grãos, polvilho azedo, soja em grãos, trigo moído e turfa. Os conídios foram quantificados em câmara de Neubauer e a determinação da viabilidade foi realizada através da observação em microscópio, dos conídios germinados e não germinados, após espalhamento da suspensão fúngica em placas de Petri contendo BDA. No ensaio com radiação os fungos foram expostos à radiação por 25 e 50 segundos e foi considerado um tratamento sem exposição; para temperatura os fungos foram expostos a 20, 25, 30 e 35o C. Utilizando a torre de Potter, 2 mL de cada suspensão fúngica dos tratamentos foram pulverizados em lagartas de D. saccharalis. As maiores concentrações de conídios de M. anisopliae e B. bassiana foram encontradas nos tratamentos com arroz parboilizado tipo 1, arroz tipo 1 e 2, farinha de milho amarela, fubá e trigo moído e a viabilidade dos conídios produzidos superou os 94%. Quanto maior o tempo de exposição à radiação menor foi o número de conídios viáveis; também ocorreu perda significativa da viabilidade dos conídios quando expostos à temperatura de 35o C. Os fungos foram patogênicos para D. saccharalis.
Semi-solid production of metarhizium anisopliae (metsch.) sorok and beauveria bassiana (bals.) vuill on different media and the effects of ultraviolet radiation and temperature on the infective propagules of these fungi
Keywords: Microbial control; Entomopathogenic fungi; Bioinsecticide; Insecta; Culture media; Controle microbiano; Fungos entomopatogênicos; Bioinseticidas; Insecta; Meios de cultura